2016
DOI: 10.1038/srep26375
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of antipsychotic-induced hyperglycaemia by vitamin D: a data mining prediction followed by experimental exploration of the molecular mechanism

Abstract: Atypical antipsychotics are associated with an increased risk of hyperglycaemia, thus limiting their clinical use. This study focused on finding the molecular mechanism underlying antipsychotic-induced hyperglycaemia. First, we searched for drug combinations in the FDA Adverse Event Reporting System (FAERS) database wherein a coexisting drug reduced the hyperglycaemia risk of atypical antipsychotics, and found that a combination with vitamin D analogues significantly decreased the occurrence of quetiapine–indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 35 publications
0
61
0
Order By: Relevance
“…There have been studies using integrative approaches of SSA and DPA to find safety signals [ 25 , 26 ]. In addition, DPA has been utilized to find unknown drug effects, for which several studies on drug repositioning have been reported [ 7 ]. In our study, an integrative approach using SSA and DPA was applied to identify repositioning opportunities for marketed drugs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been studies using integrative approaches of SSA and DPA to find safety signals [ 25 , 26 ]. In addition, DPA has been utilized to find unknown drug effects, for which several studies on drug repositioning have been reported [ 7 ]. In our study, an integrative approach using SSA and DPA was applied to identify repositioning opportunities for marketed drugs.…”
Section: Methodsmentioning
confidence: 99%
“…Inverse associations generally detected in using SSA and DPA have no meaning and are thus commonly disregarded. However, we noted that inverse associations between target drugs and AEs are often present, which suggest potential alternative therapeutic opportunities [ 7 ]. To our knowledge, there are several reports on evaluation of these inverse associations for their benefits to other methodologies such as drug-repositioning approaches [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose uptake 2-NBDG uptake was performed as previously described (Nagashima et al, 2016) with some modifications. Cells (3 Â 10 4 cells) were seeded in a 96-well black plate.…”
Section: Subcellular Fractionationmentioning
confidence: 99%
“…But is there any way to utilize shared data in basic studies related to pharmaceutical sciences? In this review, based on our experiences published in 2016, 1) we show how to process clinical evidence for the promotion of basic research, and propose new methods for developing drug discovery.…”
Section: Introductionmentioning
confidence: 99%